AUDIT ENERGI PADA GEDUNG ORANGE DAN GEDUNG BELAKANG ORANGE FAKULTAS EKONOMI DAN BISNID DI UNIVERSITAS TEKNOLOGI SUMBAWA - Bil, Habil; Ariyanto, Nova; d, Indra; Ali Topan, Paris (Program Studi Teknik Elektro, 2024)
Energy electricity drier Now become need tree for human. Supply energy standard electricity _ And each other related is strict conditions _ And must fulfil achievement objective development. University Sumbawa Technology (UTS) as Wrong One consumer energy electricity presumably need energy audit _ For save cost usage electricity, wrong one in the building Orange and Building Behind Orange (GBO). To know is consumption electricity Already fulfil level efficient or no, then from That need exists analysis opportunity to save electricity through energy audits. From the results obtained through the methods of measurement, processing, analysis and observation, the energy consumption intensity values (IKE) of the Orange Building and the Orange Rear Building in general are . With the IKE value for air-conditioned rooms, the average value is 7.07660456 kWh/m 2 / month and for non-AC rooms, the average value is 6.860981861 kWh / m 2 / month. Broadly speaking, from the rooms in the Orange Building and the Orange Back Building, it can be concluded that the categories are very efficient to efficient, but several rooms are still categorized as wasteful, namely the GO 2 room with an IKE value of 18.992 kWh/m 2 / month, and canteen room 20.73059361 kWh/m 2 / month. Until it is necessary to carry out savings opportunities. For rooms that are categorized as wasteful, it can be concluded that energy saving opportunities can be carried out by: Reducing power consumption operations, such as power consumption and hours of use.